Digital Adoption by Agri-Based Enterprises in District Jammu : Benefits and Barriers - Bakshi, Avantika (AMC Indian Journal of Entrepreneurship, 2020)
The pervasiveness and ubiquity of technology have brought significant changes in customer behavior and preferences. In light of the rapidly changing social, psychological, and recently, health-related paradigm, diffusion of technology is becoming more of a necessity. In the business context, digital metamorphosis has changed the dynamics of buyer-seller relationships around the world, irrespective of the size and scale of operations. However, this change has been non-uniform and highly versatile with consumer-based businesses showing greater acceptance and digital orientation than B2B businesses. Underlying the significance of digital technologies for adapting to the new normal in the agri-business context in India, this paper focuses on exploring the benefits and barriers of digital adoption by agriculture based (agri - based) enterprises (manufacturing/processing and trading). Findings show that technology used by businesses follows an overlapping pattern with an evident low to moderate usage of tools. Asmall percentage of businesses have shifted to advanced functions such as e-commerce. The overall perception is positive but restricted to information and communication-based functions only. In terms of hindrances, accessibility as well as lack of technical know-how drastically affects the institutionalization of such technologies.